Primary Prevention of Weight Gain Among New Bus Operators: Results of the "Success & Health Impacts For Transit operators during Onboarding" (SHIFT Onboard) Pilot Study. Issue 2 (8th February 2023) - Olson, Ryan; Rice, Sean P. M.; Bauer, Talya N.; Wipfli, Brad; Anger, W. Kent; Bodner, Todd; Graven, Peter; Greenspan, Leah S.
Abstract : An observed 12-month intervention effect (-6.71lb) from a pilot of an enhanced onboarding intervention to prevent new bus operator weight gain was at a level associated with reduced risk for developing chronic health conditions. Results support the feasibility of enhanced onboarding to prevent worsening health while advancing new employee success. Abstract : Objective: This study aimed to test the feasibility and efficacy of an enhanced onboarding intervention to prevent weight gain and support the early job success of new bus operators. Methods: Control participants ( n = 9) completed usual practice new employee training and onboarding. Intervention participants ( n = 14) completed five supplemental trainings and four online challenges during their first year. Primary outcomes were body weight, dietary behaviors, physical activity, and sleep duration/quality. Early job success was evaluated with measures of newcomer adjustment. Results: The difference between intervention and control participants in body weight change at 12-month was −6.71 lb (Cohen's d = −1.35). Differences in health behavior changes were mixed, but newcomer adjustment changes favored the intervention group. Conclusions: Results support the feasibility of enhanced onboarding for bus operators to prevent worsening health while simultaneously advancing their success as new employees.